Comprehensive monitoring of quality of electronic educational resources - Bondarenko, T. S. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the organization of monitoring the quality of electronic educational resources on the basis of the process approach, in which monitoring of the quality of resources is carried out in three directions: the quality of the project, the quality of the process and the quality of the result of their use. In connection with the multidimensional nature of the quality of electronic educational resources, it propose to carry out quality assessment based on the use of a hierarchical quality model. At the top level of this model, constructed in accordance with the process approach to management of quality, there are directions of quality monitoring. There are evaluation criteria (didactic quality of the project, methodological quality of the project, etc.) at the next level of the hierarchy of the model. They are used to assess the quality of educational resources. The criteria determine by the indicators, which in turn measure the properties (attributes) of the educational resource. The principal possibilities for measuring of the quality of electronic educational resources in the course of monitoring are considered. To evaluate their values the following methods are suggested: measuring, registration, calculation and expert method.